2021
DOI: 10.1093/bib/bbab013
|View full text |Cite
|
Sign up to set email alerts
|

m6A regulator-mediated methylation modification patterns and characteristics of immunity and stemness in low-grade glioma

Abstract: m6A RNA methylation is an emerging epigenetic modification, and its potential role in immunity and stemness remains unknown. Based on 17 widely recognized m6A regulators, the m6A modification patterns and corresponding characteristics of immune infiltration and stemness of 1152 low-grade glioma samples were comprehensively analyzed. Machine-learning strategies for constructing m6AScores were trained to quantify the m6A modification patterns of individual samples. Here, we reveal a significant correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 51 publications
3
49
0
Order By: Relevance
“…NAT10, the only confirmed regulator of mRNA acetyltransferase, shows remarkable correlation with most cancers in immune infiltration. However, as in the case of m6A RNA methylation regulators which change the levels of m6A in immune infiltration of cancers ( 35 , 36 ), the details of the molecular mechanism of NAT10 involved in the acetylation of mRNA are not clear. We tried to screen out the targeting NAT10-binging proteins and the NAT10-correlated genes for in-depth pathway enrichment analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NAT10, the only confirmed regulator of mRNA acetyltransferase, shows remarkable correlation with most cancers in immune infiltration. However, as in the case of m6A RNA methylation regulators which change the levels of m6A in immune infiltration of cancers ( 35 , 36 ), the details of the molecular mechanism of NAT10 involved in the acetylation of mRNA are not clear. We tried to screen out the targeting NAT10-binging proteins and the NAT10-correlated genes for in-depth pathway enrichment analyses.…”
Section: Resultsmentioning
confidence: 99%
“…As in the case of m6A RNA methylation regulators, it has been reported that m6A regulators play independent role of immune infiltration in several types of cancers ( 35 , 36 , 39 ). In this study, we first presented the evidence of the potential correlation between NAT10, RNA acetylation regulator, with immune infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…Bo Zhang and colleagues demonstrated that modification of m6A methylation is involved in the regulation of the microenvironment of gastric cancer, and has a guiding role in immunotherapy ( 46 ). Jianyang Du and coworkers revealed that m6A regulators had different modification patterns and characteristics of immunity in low-grade glioma ( 47 ). Most studies have focused on m6A modification, the overall TME characterization mediated by mt-rRNA modification and its regulators is not recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high ALKBH5 levels in colon cancer indicates poor prognosis ( Huang et al, 2021 ). In addition, numerous studies used the m 6 Ascore to investigate the potential clinical implications of m 6 A RNA modification patterns in cancer ( Zhang B. et al, 2020 ; Du et al, 2021 ; Shen et al, 2021a ; Xu et al, 2021b ). For example, Zhang C. et al (2020) indicated that the m 6 Ascore can act as an independent prognostic biomarker in gastric cancer.…”
Section: Potential Clinical Implications Of M 6 a Rna Modification In Cancersmentioning
confidence: 99%